Inflammation and coagulation in atherosclerosis - Krychtiuk, K. A.; Kastl, S. P.; Speidl, W. S.; Wojta, J. (Hämostaseologie, 2013)
Cardiovascular diseases remain to be the leading cause of death in Western societies. Despite major findings in vascular biology that lead to a better understanding of the pathomechanisms involved in atherosclerosis, treatment of the disease has only changed slightly within the last years. A big body of evidence suggests that atherosclerosis is a chronic inflammatory disease of the vessel wall. Accumulation and peroxidation of LDL-particles within the vessel wall trigger a strong inflammatory response, causing macrophage and T-cell accumulation within the vessel wall. Additionally, B-cells and specific antibodies against LDL-particles, as well as the complement system are implicated in atherogenesis. Besides data from clinical trials and autopsy studies it was the implementation of mouse models of atherosclerosis and the emerging field of direct genmodification that lead to a thorough description of the pathophysiological mechanisms involved in the disease and created overwhelming evidence for a participation of the immune system. Recently, the cross-talk between coagulation and inflammation in atherogenesis has gained attention. Serious limitations and disparities in the pathophysiology of atherosclerosis in mice and men complicated the translation of experimental data into clinical practice. Despite these limitations, new anti-inflammatory medical therapies in cardiovascular disease are currently being tested in clinical trials.
Keywords: Inflammation; atherosclerosis; CRP